Systematic Classification of Dental Anatomical Variations and Their Impact on the Complexity of Simple Extractions - Malik, Saman; Hassan, Faiqa; Haroon, Azka; Gul, Ambreen; Bari, Nauman; Yasir, Ayesha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To categorize anatomical variations into mild, moderate, and difficult extraction scenarios, thereby providing valuable insights to new general practitioners for appropriate treatment planning before the start of the procedure to lessen post-op complications like swelling, pain, limited mouth opening, and dry socket. Study Design: Cross-Sectional Study. Place and Duration of Study: Oral Maxillifacial Department, HITECH, Taxilla Pakistan, from Feb to Apr 2024. Methodology: The study was conducted by sharing the Google form-based questionnaire among 400 dental surgeons, specialists, and consultants to give their opinions regarding the difficulty of the extraction procedure. Results: Our study showed that 90% of clinicians reported dilaceration with maximum extraction difficulty, and 87% considered taurodontium with mild difficulty for extraction. Conclusion: Our study provides a comprehensive understanding of anatomical variations in tooth structure, offering a detailed overview for dental practitioners, especially in practical settings, and culminating in the development of a practical guide to enhance treatment planning and outcomes. Moving forward, continuous research and collaboration within the dental community can further refine and expand upon these findings to continually improve clinical practices and patient outcomes.